Was Singapore extraordinary? A comparative view of Singapore's saving performance 1965-99 - Gregor Hopf (Hamburg School of Business Administration (HSBA), 2009)
Although the mere observation of saving aggregates might have us believe differently, this article argues that Singapore's sustained high saving performance was far from extraordinary once the country's particular circumstances are econometrically controlled for. Singapore's saving performance should therefore not be regarded as a mere blip in economic history. As a matter of fact, not the high saving rates in the late 1980s and 1990s, which usually attract the most attention, but rather the speed of transformation of the country's saving behaviour in the first years of independence is shown to be indeed extraordinary. Singapore was able to overcome its low initial saving performance much faster and much more strongly than could have been expected given its circumstances.
Keywords: 650; Asia; Singapore; saving rate; economic growth